Diet and ecomorphological relationships of four cichlid species from the Cuiabá River basin - Gisele C. Novakowski; Fernanda A. S. Cassemiro; Norma S. Hahn (Neotropical Ichthyology)
ABSTRACT Relationship between diet and morphology of cichlid were analyzed considering that the trophic apparatus determines differential food use among species. Cichlasoma dimerus and Satanoperca pappaterra showed a generalist diet, while Chaetobranchopsis australis and Crenicichla vittata consumed zooplankton and fish, respectively. Significant correlation between morphology and diet was not found, but C. australis differed from the others species in the upper mouth and longer gill rakers. The morphology data and food size segregated the cichlids into three groups. The first was comprised by C. australis, which has many and longer gill rakers and a more protractile mouth, the second by C. vittata, which have a larger and more-protruded mouth and the third by S. pappaterra and C. dimerus, with a smaller and lower mouth. The latter two groups have more widely spaced gill rakers and consumed larger food. Overall, our results showed different patterns of species grouping when considering morphological or diet data. However, to C. australis the gill rakers determine both the type and size of food.